Ab initio analysis of magnetic properties of the prototype B20 chiral magnet FeGe - Grytsiuk, S.; Hoffmann, M.; Hanke, J-P; P. Mavropoulos; Mokrousov, Y.; Bihlmayer, G.; S. Blügel (PHYSICAL REVIEW B, 2019)
FeGe in the B20 phase is an experimentally well-studied prototypical chiral magnet exhibiting helical spirals, skyrmion lattices, and individual skyrmions with a robust length of 70 nm. While the helical spiral ground state can be verified by first-principles calculations based on density functional theory, this feature size could not be reproduced even approximately. To develop a coherent picture of the discrepancy between experiment and theory, we investigate in this work the magnetic properties of FeGe from first principles using different electronic-structure methods. We study atomistic as well as micromagnetic parameters describing exchange and Dzyaloshinskii-Moriya interactions, and discuss their subtle dependence on computational, structural, and correlation parameters. In particular, we quantify how these magnetic properties are affected by changes of the lattice parameter, different atomic arrangements, exchange and correlation effects, finite Fermi-function broadening, and momentum-space sampling. In addition, we use the obtained atomistic parameters to determine the corresponding Curie temperature, which agrees well with experiments. Our results indicate that the well-known and well-accepted relation between the micromagnetic parameters and the period of the helical structure is not valid for FeGe. This calls for new experiments exploring the relation by measuring independently the spin stiffness, the spiralization, and the period of the helical spin spiral.